Synchronized beamline at FLASH2 based on high-order harmonic generation for two-color dynamics studies - Appi, Elisa; Papadopoulou, C. C.; Mapa, J. L.; Jusko, C.; Mosel, P.; Schoenberg, A.; Stock, J.; Feigl, T.; Ališauskas, S.; Lang, T.; Heyl, C. M.; Manschwetus, B.; et al. (Review of scientific instruments, 2021)
We present the design, integration, and operation of the novel vacuum ultraviolet (VUV) beamline installed at the free-electron laser (FEL) FLASH. The VUV source is based on high-order harmonic generation (HHG) in gas and is driven by an optical laser system synchronized with the timing structure of the FEL. Ultrashort pulses in the spectral range from 10 to 40 eV are coupled with the FEL in the beamline FL26, which features a reaction microscope (REMI) permanent endstation for time-resolved studies of ultrafast dynamics in atomic and molecular targets. The connection of the high-pressure gas HHG source to the ultra-high vacuum FEL beamline requires a compact and reliable system, able to encounter the challenging vacuum requirements and coupling conditions. First commissioning results show the successful operation of the beamline, reaching a VUV focused beam size of about 20 µm at the REMI endstation. Proof-of-principle photo-electron momentum measurements in argon indicate the source capabilities for future two-color pump-probe experiments.